Career, Family, and IVF: The Impact of Involuntary Childlessness and Fertility Treatment - Fabio I. Martinenghi; Maryam Naghsh Nejad (Institute of Labor Economics (IZA), 2025)
We use whole-population linked administrative data from Australia to ex- amine the economic and mental health impacts of IVF treatment and invol- untary childlessness. Leveraging detailed information on fertility treatment, income, and prescription drug use, we implement a dynamic triple-difference framework comparing women who remain childless five years after initiating IVF to those who successfully conceive. Results reveal large and persistent effects on both mental health and income. We further show that the IVF process itself leads to income declines among childless women, underscoring substantial unmeasured costs and suggesting downward bias in child penalty estimates that use unsuccessful IVF patients as controls.
Keywords: J13; J22; I14; I31; J16; 330; labor market outcomes; mental health; IVF; involuntary childlessness; fertility and career trade-offs